HUBUNGAN KONSUMSI SUGAR-SWEETENED BEVERAGES (SSBS) DAN PEMESANAN MAKANAN BERISIKO SECARA ONLINE DENGAN KADAR GLUKOSA DARAH PEKERJA USIA 25-44 TAHUN DI PERUMAHAN KASUARI, CIKARANG - Agatha Katherine Widi Puspita Jayanti, (2021)
25-44 years are the productive age to work and still can prevent diabetes mellitus by maintaining blood sugar levels. The increase of blood glucose levels can be caused by consuming high Sugar-Sweetened Beverages (SSBs) and often order food by online that contain a lot of sugar, salt, dan fat (risky foods). The aim of this research was to find out correlation of consuming SSBs and online risky foods ordering to employee aged 25-44 years blood glucose levels in Kasuari, Cikarang. The method used in this research is cross sectional. The respondents are 47 employees aged 25-44 years who live in Kasuari, Cikarang and fulfill the inclusion criteria. Blood glucose levels is measured with glucometer. Data of consuming SSBs is obtained by interview with Semi-Quantitative Food Frequency Questionnaire form (SQ-FFQ), while online food order is obtained with FFQ form. After processing and analyze data, the following results are there is correlation between consuming SSBs, online high sugar foods ordering, and online risky foods ordering with blood glucose levels (p value = 0,044 ; 0,001 ; 0,008). There is no correlation between online high salt foods and high fat foods ordering with blood glucose levels (p value = 0,184 and 0,079).